A comparative analysis and evaluation of PEN-3 cultural model and Leininger's theory - U.C. Opara; S. Bassendowski; P. Petrucka (Elsevier, 2024)
Using a theoretical framework in nursing research is vital to promote understanding of a theory, its major concepts, and the relationship between concepts in research. We propose to conduct a study focusing on "Women's Experiences of Cultural Beliefs and Practices that Influence Their Use of Maternal Health Services in Nigeria." The PEN-3 cultural model, a non-nursing theory that exhibits the characteristics of mid-range nursing theories, will be used as a theoretical framework. As a nursing research, Leininger's Culture Care Diversity and Universality Theory also known as Culture Care Theory would have been best suited for the proposed research. However, as a grand theory, the Culture Care Theory has limited applicability in the proposed study due to its abstraction and complexity. A critical analysis and evaluation of both theories were conducted to enhance a deep understanding of the PEN-3 cultural model and the Culture Care Theory in supporting the proposed research. This critical evaluation is vital, especially for potential users of the PEN-3 cultural model, to understand the model's potential usefulness in guiding nursing research and explaining nursing situations.